#### Answer

$s'(t) = -6t$
So,
$s'(-1) = 6$

#### Work Step by Step

$s(t) = 1-3t^{2}$
Therefore,
$s'(t) = 0 - 3(2)t^{2-1}$
$s'(t) = -6t$
So,
$s'(-1) = 6$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$s'(t) = -6t$
So,
$s'(-1) = 6$

$s(t) = 1-3t^{2}$
Therefore,
$s'(t) = 0 - 3(2)t^{2-1}$
$s'(t) = -6t$
So,
$s'(-1) = 6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.